Activation of CCL21-GPR174/CCR7 on cardiac fibroblasts underlies myocardial ischemia/reperfusion injury - Meng, Xiao-Wen; Zhang, Mian; Hu, Jun-Kai; Chen, Xin-Yu; Long, Yu-Qin; Liu, Hong; Feng, Xiao-Mei; Ji, Fu-Hai; Peng, Ke (Frontiers in Genetics, 2022)
Background: The mechanisms underlying myocardial ischemia/reperfusion (I/R) injury are not fully understood. This study aims to explore key candidate genes and potential therapeutic targets for treatment of myocardial I/R injury. Methods: The transcriptional profiles of ventricular myocardium during cardiac arrest, ischemia, and reperfusion were obtained from the Gene Expression Omnibus database. Based on the transcriptional data of GSE6381, functional pathway and process enrichment analyses, protein–protein interaction network, and gene set enrichment analyses were conducted. In the animal experiments, we established the myocardial I/R injury model in mice. We validated the mRNA and protein expression of the key genes using the qPCR and western blots. We further assessed the expression and localization of CCL21 and its receptors using immunofluorescence staining experiments. Results: The microarray analyses identified five key genes (CCL21, XCR1, CXCL13, EDN1, and CASR). Myocardial I/R process in mice resulted in significant myocardial infraction, histological damage, and myocardial apoptosis. The results of qPCR and western blots showed that the expression of CCL21 and CXCL13 were increased following myocardial I/R injury in mice. Furthermore, the immunofluorescence staining results revealed that the expression of GPR174/CCR7 (CCL21 receptors), but not CXCR5 (CXCL13 receptor), was elevated following myocardial I/R injury. Moreover, the activated CCL21-GPR174/CCR7 signaling was located on the cardiac fibroblasts of the myocardium with I/R injury. Conclusion: This study revealed several key factors underlying myocardial I/R injury. Of these, the activation of CCL21-GPR174/CCR7 signaling on cardiac fibroblasts was highlighted, which provides potential therapeutic targets for cardioprotection.